Towards a generic Agent-based Simulation model for time-constrained tasks - Nguyen T.D.; Tang A.Y.C.; Ahmad A. (IEEE Computer Society, 2023)
Documentation processing workflow presents in daily life business and these tasks are adhered to stipulated time-frame. Most of the agent-based simulation systems in this area are customized to a domain specific problem. A generic agent-based simulation model is expected to help verify, assess and validate processes or tasks in time-constrained workflow management. This paper reviews some domain-specific workflows and motivates the needs for a generic Agent-based Simulation (ABS) model for time-constrained process tasks. Based on the review results, we propose a plan and preliminary parameters for developing a conceptual model for the generic ABS simulation in such environment. © 2013 IEEE.